Wavelet based distortion measurement and enhancement of ECG signal - Md. Abdul, Awal; Mohiuddin, Ahmad, Prof. Dr. Engr.; Ismail, Daut, Prof. Dr.; Ernie, Che Mid; Mohd. Abdur, Rashid, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/